Expanding the scope of social science research on disability - Altman, Barbara Mandell; Barnartt, Sharon N. (Research in social science and disability, 2000)
The first volume presents a collection of exciting papers exploring several new areas of disability research. The contributions include: examination of the media representation of disability and coverage of disability policy issues which gives an understanding of the far reaching impact of the fourth estate; an historical analysis of the correspondence between the identifier of Down syndrome and Darwin that lends insights into the development of interpretations of mental retardation particularly Down syndrome as a throwback to the more primitive nature of man; analysis of hospital discharge data which demonstrates that persons with chronic conditions and impairments are more likely than those without to need hospitalization for injuries resulting from violence; and an overview of voting behavior among persons with disabilities. Subsequent volumes will focus on specific subjects related to disability issues.